2022
DOI: 10.1021/acs.est.2c05735
|View full text |Cite
|
Sign up to set email alerts
|

A Bipolar Membrane-Integrated Electrochlorination Process for Highly Efficient Ammonium Removal in Mature Landfill Leachate: The Importance of ClO Generation

Abstract: Electrochemical oxidation has been demonstrated to be a useful method for removing biorefractory organic pollutants in mature landfill leachate but suffers from low efficiency in eliminating ammonium because of its resistance to being oxidized by HO • or free chlorine (FC) at decreased pH. Here, we propose a new bipolar membrane-electrochlorination (BPM-EC) process to address this issue. We found that the BPM-EC system was significantly superior to both the undivided and divided reactors with monopolar membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…It is visible that the concentration of NH 4 + -N consistently decreased over time during electrolysis, regardless of the initial content (ranging from 20 to 500 mg L –1 ) (Figure S14a). The linear curves displayed similar slopes, indicating a zero-order reaction kinetics. ,, This finding further supports the conclusion that the predominant reaction facilitated by Cl • primarily occurs within the bulk solution rather than at the surface because of its relatively long lifespan (∼10 –6 s). , A minimal NH 4 + -N loss occurred when the electrolyte did not contain Cl – (Figure S14b), suggesting that direct anodic oxidation and HO • -initiated reactions were not favorable for the oxidation of NH 4 + -N. This observation aligns with existing literature on the subject. , The addition of Cl – into the system resulted in a significant enhancement of the NH 4 + -N removal rate, attributable to the increased levels of reactive chlorine species generated. However, the extent of improvement diminished as the Cl – concentration surpassed 50 mM, indicating that the reaction became limited by charge transfer rather than mass transfer. , Interestingly, at a Cl – concentration of 500 mM, the reaction was slightly inhibited, potentially due to the reaction between Cl • and excessive Cl – resulting in the production of Cl 2 •– , a species resistant to oxidizing NH 4 + -N, as elaborated in the previous section.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…It is visible that the concentration of NH 4 + -N consistently decreased over time during electrolysis, regardless of the initial content (ranging from 20 to 500 mg L –1 ) (Figure S14a). The linear curves displayed similar slopes, indicating a zero-order reaction kinetics. ,, This finding further supports the conclusion that the predominant reaction facilitated by Cl • primarily occurs within the bulk solution rather than at the surface because of its relatively long lifespan (∼10 –6 s). , A minimal NH 4 + -N loss occurred when the electrolyte did not contain Cl – (Figure S14b), suggesting that direct anodic oxidation and HO • -initiated reactions were not favorable for the oxidation of NH 4 + -N. This observation aligns with existing literature on the subject. , The addition of Cl – into the system resulted in a significant enhancement of the NH 4 + -N removal rate, attributable to the increased levels of reactive chlorine species generated. However, the extent of improvement diminished as the Cl – concentration surpassed 50 mM, indicating that the reaction became limited by charge transfer rather than mass transfer. , Interestingly, at a Cl – concentration of 500 mM, the reaction was slightly inhibited, potentially due to the reaction between Cl • and excessive Cl – resulting in the production of Cl 2 •– , a species resistant to oxidizing NH 4 + -N, as elaborated in the previous section.…”
Section: Resultssupporting
confidence: 86%
“…Our previous studies and relevant literature have shown that the oxidation of NH 4 + by free chlorine under acid conditions exhibits sluggish kinetics. ,, For instance, the rate constant has been reported to be less than 10 2 M –1 s –1 at pH < 4.0 . To further confirm this, a series of reference experiments were performed in the same pH range and by directly mixing NH 4 + with HClO at different concentrations.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations